Understanding the Dynamics of Business Incubators and Their Influence on Startup Performance in India - Razak, Abdul; ., Vasumathi A; Vasudevan, Asokan; Mcxin , Tee; Ramachandaran, Sharmila Devi; Krishnasamy, Hariharan N (Journal of Ecohumanism, 2024)
Business Incubation Centers (BICs) are vital in supporting new entrepreneurs by providing essential infrastructure, mentorship, and funding to help them build successful businesses. This study examines how BICs contribute to the growth and sustainability of startups, particularly in India, where they are essential for economic development. Through initiatives like the Make in India and Start-up India schemes, the Indian government has bolstered the startup ecosystem, promoting job creation and economic growth. These government-supported programs empower BICs, which foster innovation, entrepreneurial skills, and knowledge in a supportive environment. Focusing on startups in Hyderabad, Chennai, and Bangalore, this study explores the impact of BICs on business performance and success, highlighting the need for policies that adapt to new challenges and market changes. By nurturing startups, India aims to reduce unemployment and poverty while enhancing productivity and global competitiveness. With an ever-evolving approach to entrepreneurship, the country is positioning itself as a significant player in the global startup landscape, leveraging BICs to accelerate economic growth and build a robust, sustainable economy.